2020
DOI: 10.3389/fcell.2020.00202
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Derived Human-miRNAs Modulate the Immune System in Type 1 Diabetes

Abstract: Extracellular vesicles with their molecular cargo can modulate target cell response and may affect the pathogenesis of diseases. The extracellular vesicles containing micro-RNAs (miRNAs), which are often studied as disease biomarkers, but rarely as mediators of the disease development. The role of extracellular vesicles derived miRNAs in type 1 diabetes is currently not well established. We observed a fraction of blood plasma extracellular vesicles positive for membrane proteins potentially associated with ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 86 publications
0
34
0
1
Order By: Relevance
“…miR-129-5p was significantly overexpressed in Langerhans islets transplantation patients [80]. The expression of miR-129 was significantly downregulated in CRC tissue specimens compared with the paired normal control samples [81].…”
Section: Microrna Biomarkersmentioning
confidence: 93%
“…miR-129-5p was significantly overexpressed in Langerhans islets transplantation patients [80]. The expression of miR-129 was significantly downregulated in CRC tissue specimens compared with the paired normal control samples [81].…”
Section: Microrna Biomarkersmentioning
confidence: 93%
“…Further studies have shown that co-incubation of diabetic EVs with monocytes could reduce the expression of genes related to apoptosis and oxidative stress in monocytes ( 36 , 58 ). It also increased the expression of many proinflammatory cytokines ( 58 60 ). These findings suggest that EVs in diabetic patients promote monocyte survival and promote monocyte inflammatory activation.…”
Section: Effects Of Exosomes In Diabetes Mellitusmentioning
confidence: 97%
“…Regardless of the approach, WGS or targeted, there are some properties of the human genome being uncovered, that neither could be detected without complex technical modifications or a special type of human genome analysis. The role of epigenetics and non-coding RNAs on the expression of genes is just starting to be discovered (Tesovnik et al, 2020). The role of topologically associated domains and interchromosomal interactions and the influence of the 3D structure of the genome in the expression of genes and potential cause of the disease are still not fully understood (Maass et al, 2018(Maass et al, , 2019.…”
Section: Technical Feasibilitymentioning
confidence: 99%